1987
DOI: 10.1203/00006450-198704000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Lipid Abnormalities in Reye's Syndrome

Abstract: ABSTRACT. Previous studies have demonstrated alterations in plasma free fatty acid content in Reye's syndrome (RS). We have therefore studied erythrocyte membrane lipids to determine if there are concomitant structural and functional modifications attributable to RS. Erythrocyte lipids were measured in children with RS and in critically ill children also requiring intensive care (ICU). In comatose RS patients erythrocyte phospholipid arachidonate was increased 2-fold relative to control ICU patients: 20.46 f 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The mechanism of this increase is unclear. The increase in free fatty acids could be due to the activation of endogenous phospholipase activity which has been postulated previously in Reye's syndrome (54).…”
mentioning
confidence: 59%
“…The mechanism of this increase is unclear. The increase in free fatty acids could be due to the activation of endogenous phospholipase activity which has been postulated previously in Reye's syndrome (54).…”
mentioning
confidence: 59%
“…Tonsgard (1989) recently reported that serum levels of both monocarboxylic and dicarboxylic fatty acids are elevated at certain stages of the disease. There is also evidence that the relative proportions of unesterified polyunsaturated fatty acids are increased in serum (Ogburn et al, 1982) and in erythrocytes (Schwarz et al, 1987) of RS patients. Contiguous withserum lipid abnormalities, the cells of the visceral organs, particularly the liver, are loaded with fat that is stored as microvesicular droplets (Brown and Forman, 1982).…”
mentioning
confidence: 99%